E-Cadherin (CDH1) and p53 rather than SMAD4 and Caspase-10 germline mutations contribute to genetic predisposition in Portuguese gastric cancer patients - Oliveira, Carla (2004)
Approximately 30% of all hereditary diffuse gastric cancer (HDGC) families carry CDH1 germline mutations. The other two thirds remain genetically unexplained and are probably caused by alterations in other genes. Using polymerase chain reaction (PCR)/single-strand conformation polymorphism (SSCP)/sequencing, we screened 32 Portuguese families with a history of gastric cancer and 23 patients with early onset gastric cancer for CDH1 germline mutations. In probands negative for CDH1 mutations, we screened genes involved in hereditary cancer syndromes in which gastric cancer may be one of the component tumours, namely p53 (Li-Fraumeni Syndrome) and hMLH1 and hMSH2 (HNPCC). We also screened in these patients for mutations in Caspase-10, a gene inactivated in sporadic gastric cancer, and SMAD4, a gene whose inactivation in mice is associated with signet-ring cell carcinoma of the stomach. One of the families fulfilling the HDGC criteria harboured a CDH1 germline mutation, and one of the families with incomplete criteria harboured a p53 germline mutation. No mutations were identified in hMLH1 and hMSH2, and only sequence variants were found in SMAD4 and Caspase-10. The present work reports for the first time CDH1 germline mutations in Portuguese gastric cancer families, and highlights the need for p53 mutation screening in families lacking CDH1 germline mutations, in a country with one of the highest incidences of gastric cancer in the world. No evidence was found for a role of germline mutations in SMAD4 and Caspase-10 in families lacking CDH1 mutations.